Perancangan Website E-Commerce Untuk Fayucom Dengan Integrasi Payment Gateway Xendit Menggunakan Html, Css, Dan Javascript - Tafonao, Fatolosa; Setyohadi, Setyohadi; Raslina, Natalia Nadia (Jurnal Sosial Teknologi, 2025)
The fayucom.store website is a local e-commerce platform developed to meet the needs of the community in obtaining technology products and computer accessories at affordable prices. This research aims to examine the system design, main features, and website effectiveness in supporting the digital transaction process and user convenience. The research method used is descriptive qualitative method with a case study approach to the fayucom.store website. The results showed that this website has quite complete features, such as product management, automatic checkout system, admin dashboard, and responsive on various devices. However, there are still some aspects that need to be developed, especially in terms of security, SEO, and mobile display performance. With the right improvements, fayucom.store has great potential to develop as a competitive and sustainable local e-commerce. This article also provides strategic recommendations for system strengthening, payment API integration, and further UI/UX development.